72 reasons to be vegan : why plant-based, why now - Stone, Gene, 1951-; Freston, Kathy (Workman Publishing, 2021)
"Did you know that if you adopt a vegan diet you can enjoy better sex? Save money? Have glowing skin? You can ward off Alzheimer's, Type 2 diabetes, rheumatoid arthritis, and other metabolic diseases. You can eat delicious burgers. Help save the planet. Join the cool kids, like Gandhi, Tolstoy, Leonardo-and Kyrie Irving, Kat Von D, and Joaquin Phoenix. Oh, and did we mention have better sex? (It's about blood flow.) Those are just some of the 72 reasons we should all be vegan, as compiled and persuasively argued by Gene Stone and Kathy Freston, two of the leading voices in the ever-growing movement to eat a plant-based diet. While plenty of books tell you how to go vegan, 72 Reasons to Go Vegan is the book that tells you why. And it does so in a way that emphasizes not what you'd be giving up, but what you'd be gaining. The tone is upbeat, passionate, and direct, and the facts are plentiful and annotated. Whether because of environment, health, or compassion for animals, more and more people are dipping their toes into Meatless Mondays, eating vegan before 6:00 p.m., choosing Impossible Burgers, or helping books like Thug Kitchen, Forks Over Knives, and Skinny Bitch become national bestsellers-making 72 Reasons to Go Vegan the ideal next book for every food-conscious reader and the perfect gift vegans can give to their friends and family"--